Inkonstitusionalitas Pajak Bumi dan Bangunan Sektor Pertambangan Mineral dan Batubara di Indonesia - Trinandityo, Argo (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Tax shall reflect the community cooperation and participation in order to fund the nation’s development. As the main source of the country’s income, tax payment always has special treat from the law, such as the priority payment from the certain people (in example debtor) before any other payment obliged to them. Indonesia as a Nation of Laws (rechtstaat), and not a Power State (machtstaat), therefore shall to give law as the main guidance for the nation in every action. The Undang-Undang Dasar Negara Republik Indonesia 1945 (UUD 45) as the Constitution shall limit the Government power, including the power to tax. Therefore, the regulation related to tax and any levy imposed for the country must be regulated by a Law/Act. As the consequences, tax without a Law will be unconstitutional. Indonesia Land and Building Tax for Mineral and Coal Mining Sector (PBB Minerba) still referring to Law of Land and Building Tax, which has very distinguished character with the PBB Minerba itself. Until now, PBB Minerba have not regulated by a certain Law/Act as obliged by the third amendment of constitution UUD 45.